Contractile profile of esophageal and gastric fundus strips in experimental doxorubicin-induced esophageal atresia - Capeto,F.A. (2015)
Esophageal atresia (EA) is characterized by esophageal and gastric motility changes secondary to developmental and postsurgical damage. This study evaluated the in vitro contractile profile of the distal esophagus and gastric fundus in an experimental model of EA induced by doxorubicin (DOXO). Wistar pregnant rats received DOXO 2.2 mg/kg on the 8th and 9th gestational days. On day 21.5, fetuses were collected, sacrificed, and divided into groups: control, DOXO without EA (DOXO-EA), and DOXO with EA (DOXO+EA). Strips from the distal esophagus and gastric fundus were mounted on a wire myograph and isolated organ-bath system, respectively, and subjected to increasing concentrations of carbamylcholine chloride (carbachol, CCh). The isolated esophagus was also stimulated with increasing concentrations of KCl. In esophagus, the concentration-effect curves were reduced in response to CCh in the DOXO+EA and DOXO-EA groups compared to the control group (P<0.05). The maximum effect values (Emax) for DOXO+EA and DOXO-EA were significantly lower than control (P<0.05), but the half-maximal effective concentration (EC50) values were not significantly different when the three groups were compared (P>0.05). In response to KCl, the distal esophagus samples in the three groups were not statistically different with regard to Emax or EC50 values (P>0.05). No significant difference was noted for EC50 or Emax values in fundic strips stimulated with CCh (P>0.05). In conclusion, exposure of dams to DOXO during gestation inhibited the contractile behavior of esophageal strips from offspring in response to CCh but not KCl, regardless of EA induction. The gastric fundus of DOXO-exposed offspring did not have altered contractile responsiveness to cholinergic stimulation.